PENGARUH WORK LIFE BALANCE, KEPUASAN KERJA, DAN MOTIVASI KERJA TERHADAP INTENTION TO STAY KARYAWAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BINA INSAN MANDIRI KARANGANYAR - Della Arventya Vadmara; Bangun Prajadi Cipto Utomo; Nur Hadi (STKIP Subang, 2026)
This study aims to analyze the effect of Work Life Balance, Job Satisfaction, and Work Motivation on Intention to Stay among employees of Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Bina Insan Mandiri Karanganyar. This research uses a quantitative approach with a deductive method. The population consisted of 52 employees, and a saturated sampling technique was used so that all 52 employees became respondents. Primary data were collected through a Likert-scale questionnaire and analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that Work Life Balance has a positive but insignificant effect on Intention to Stay, while Job Satisfaction also has a positive but insignificant effect. Work Motivation has a positive and significant effect on Intention to Stay and is the most dominant predictor in the regression model. Simultaneously, Work Life Balance, Job Satisfaction, and Work Motivation have a significant effect on Intention to Stay. The coefficient of determination indicates that 61.2% of the variation in Intention to Stay is explained by the three independent variables, while the remaining 38.8% is explained by other factors outside the research model.